THE SALT CRYSTALLIZATION WEATHERING OF BUILDING ROCKS OF THE ARCHAEOLOGICAL SITES CALCARENITES OF NORTH-WESTERN MOROCCO (LIXUS, BANASA AND THAMUSIDA) - Ouacha, H.; Ben Moussa, A.; Simao, J. (European Scientific Journal, ESJ, 2013)
The archeological cities of north-western Morocco: Lixus, Banasa and Thamusida represent an international heritage, with a great social and cultural importance for the history of the country. This work is dedicated to study the salt crystallization weathering, reaching the building rocks of the monuments in order to preserve and restore them. These monuments show a variety of lithological facies implemented in its construction. The degradation of these materials is accelerated by climate influence of El Gharb and Prerif area, characterized by a high humidity and an important atmospheric and soil salinity. The most affected building rocks by the weathering are generally represented by limestones (calcarenites). When salt crystallizes in the pores of the rock after evaporation, the crystal dissociates the grains surrounding by expansion. Therefore, there is a loss of material. The accelerated aging test laboratory shows that calcarenites present the highest rate of weight loss among the samples of different lithologies. This is rendered in a significant susceptibility to degradation; a physical degradation by salt crystals expansion and a chemical degradation by a carbonates dissolution in the presence of the saline fog and a high temperature (50 °C). Lixus calcarenites are more resistant to weathering by salt, when compared to the calcarenites of the other two monuments.